Faster through training: The anammox case. (15th September 2015) - Lotti, T.; Kleerebezem, R.; Abelleira-Pereira, J.M.; Abbas, B.; van Loosdrecht, M.C.M.
Abstract: Anaerobic ammonium oxidizing (anammox) bacteria based technologies are widely applied for nitrogen removal from warm (25–40 °C) wastewater with high ammonium concentrations (∼1 gNH4 –N L −1 ). Extension of the operational window of this energy and resource efficient process is restricted by the "supposed" low growth rate of the responsible microorganisms. Here we demonstrate that the maximum specific growth rate ( μ max ) of anammox bacteria can be increased to a μ max value of 0.33 d −1 by applying a novel selection strategy based on the maximization of the electron transfer capacity in a membrane bioreactor. This value is four times higher than the highest previously reported value. The microbial community was strongly dominated by anammox bacteria closely related (99%) to Candidatus Brocadia sp.40 throughout the experiment. The results described here demonstrate the remarkable capacity of a phylogenetically stable anammox community to adjust its growth rate in response to a change in the cultivation conditions imposed. Graphical abstract: Highlights: Novel selection strategy based on maximization of the electron transfer capacity. Three times increase in specific ammonium uptake rate during cultivation. Highest (four times higher) directly estimated growth rate of 0.334 d −1 (at 30 °C). No shift in dominant anammox strain nor major mutations in the dominant strain. Demonstration that maximum growth rate is not an intrinsic process property.